Dry Eye After Phacoemulsification - Munish Dhawan; Gagandeep Kaur; S.P. Singh (Delhi Journal of Ophthalmology)
Background:- Dry eye is a multifactorial, heterogeneous disorder of the preocular tear film because of tear deficiency or excessive tear evaporation which causes symptoms of ocular discomfort. Many patients who have undergone cataract surgery have complained of dry eye and symptoms of irritation postoperatively. The aim of this study was to evaluate the incidence and severity pattern of dry eye after phacoemulsification. Design:- Prospective study. Materials & Methods:- 100 uncomplicated cataract patients coming to Guru Gobind Singh Medical College and Hospital, Faridkot were selected for study. Dry eye incidence and pattern were analyzed preoperatively and at days 1, 7, 30 and 90 after phacoemulsification using (1) Ocular Surface Disease Index (OSDI) questionnaire, (2) tear break up time (TBUT), (3) rose bengal staining, (4) Schirmer I test without anesthesia and (5) Schirmer 2 test with anesthesia. Data was evaluated by student T test. Results:- Seven days after phacoemulsification, the incidence of dry eye was 11%. The severity of dry eye peaked seven days post-phacoemulsification and was measured by OSDI questionnaire and all four clinical tests. Within 30 days and 3 months post-surgery, both the symptoms and signs showed rapid and gradual improvements respectively. Conclusions:- The incidence of dry eye after phacoemulsification was 11%. Symptoms and signs of dry eye occurred as early as seven days post-phacoemulsification and the severity pattern improved over time. We recommend that ophthalmologists should evaluate patients both before and after phacoemulsification to prevent further damage to the ocular surface and manage the patient promptly and effectively so that the patient does not have a poor quality of life and vision due to dry eye syndrome.